Successful Co-Feeding of Asian Seabass, Lates calcarifer Larvae With Palm Oil-Based Microdiets and Live Feeds - Safiin, Nik Siti Zaimah; Ching, Fui Fui; Shapawi, Rossita (Frontiers in Sustainable Food Systems, 2022)
Weaning microdiets for Asian seabass larvae were formulated with dietary fish oil being replaced with crude palm oil, CPO at 25%, 50% and 75% (CPO25, CPO50 and CPO75) and refined bleached deodorized palm olein, RPO at 50% and 75% (RPO50, RPO75) replacement levels. A fish-oil based microdiet was used as a control treatment (FO100). Triplicate groups of fish larvae with initial weight and length of 1.71±0.13 mg and 5.54±0.34 mm, respectively were co-fed with the experimental microdiets and live feeds for 33 days. The growth performance of fish fed palm oil-based diets were significantly better (0.54-0.63 g) than the control diet (0.42 g), with RPO75 yielded the best performance in growth. Survival rate of larvae fed palm oil based-diets (33.11-46.67%) during the feeding trial was comparable to the control diet (39.33%). In the salinity test, there was no significant difference in term of survival rate of larvae fed the control diet and the CPO-based diets, but lower survival rate was observed in the RPO-based diets than the control diet. The body proximate and fatty acid profile of the larvae were also significantly affected by the dietary treatments. Considering the good growth and survival of larvae Asian seabass in the present study, availability of palm oil and its competitive price compared to fish oil, it is suggested that weaning diets for Asian seabass larvae can be developed using palm oil as a partial source of dietary lipid.